CEZA MUHAKEMESİNDE UZLAŞTIRMACININ ÖZELLİKLERİ VE UYMASI GEREKEN ETİK İLKELER - (:unkn) unknown (My University, 2018)
5271 Sayılı Ceza Muhakemesi Kanunu’nda düzenlenen uzlaştırmakurumuna ilişkin yapılan son yasal değişikliklerle birlikte, uzlaştırmanınceza muhakemesi sistemimizdeki önemi ve işlevi artmıştır. Mağdur, fail,toplum bakımından pek çok faydası bulunan bu müessese, yargının işyükünü azaltması sebebiyle de yargı sistemimize önemli bir katkı sağ-lamaktadır. 2016 yılında getirilen düzenlemelerle, uzlaşma teklif ve mü-zakere süreci tümüyle uzlaştırmacıya bırakılmıştır. Uzlaştırmacı olabil-mek için eğitim ve yazılı sınavda başarılı olma koşulları getirilmiştir.Ayrıca Uzlaştırma Yönetmeliğinde uzlaştırmacının uyması gereken etikilkeler ayrıntılı şekilde düzenlenmiş ve bu ilkelere aykırılık neticesindeuygulanacak yaptırımlar belirlenmiştir.

With the recent legislative amendments made to the reconciliation institution set forth in the Criminal Procedure Code No. 5271, the reme- dy has increased its importance and function in our criminal procedure system. This institution, which has many benefits for the victim, the per- petrator, the society, makes a significant contribution to our judicial system because of the reduction of workload of the judiciary. With the arrangements introduced in 2016, the compromise proposal and negoti- ation process has been left to fully conciliator. In order to become a conciliator, conditions for success in education and written exam have been introduced. In addition, in the Reconciliation Regulations, the ethi- cal principles that the conciliator must comply with are detailed and the sanctions to be imposed on these principles are determined.
THE CHARACTERISTICS OF THE CONCILIATOR IN THE CRIMINAL PROCEDURE AND THE ETHICAL PRINCIPLES TO BE BIND
Keywords: Hukuk